2017
DOI: 10.1039/c6ta10978k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and side-chain engineering of phenylnaphthalenediimide (PNDI)-based n-type polymers for efficient all-polymer solar cells

Abstract: We designed and synthesized a series of n-type conjugated polymers by introducing phenylnaphthalenediimide (PNDI) as a novel n-type building block, and investigated the effect of side-chain engineering in the polymer acceptor on the performance of all-polymer solar cells (all-PSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…As stated in earlier section and previous reports, conjugated polymers with shorter and linear alkyl side chains possess more pronounced, densely packed molecular ordering in thin films, and may perform better in devices. However, conjugated polymers with one shorter alkyl side chain usually suffer from poor solubility in common organic solvents.…”
Section: Resultssupporting
confidence: 69%
“…As stated in earlier section and previous reports, conjugated polymers with shorter and linear alkyl side chains possess more pronounced, densely packed molecular ordering in thin films, and may perform better in devices. However, conjugated polymers with one shorter alkyl side chain usually suffer from poor solubility in common organic solvents.…”
Section: Resultssupporting
confidence: 69%
“…One of the major challenges in the development of organic electronics is increasing the charge-carrier mobility [1,2,3,4]. Since charge transport in the constituent materials of organic electronics is an essential property, this phenomenon has been widely studied by using organic field-effect transistors as a platform of investigation [19,20]. Charge transport in organic semiconductor films is known to depend strongly on the crystalline structure, molecular orientation, and morphology of the films [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that introducing bulky phenyl rings showed minimal effects on the polymer π‐conjugation length. Among the series, 47 b with 2‐butyloctyl chain displayed a well‐organized packing structure and favorable domain size when mixed with D1 polymer, leading to the highest PCE of 4.25 % . Chen et al.…”
Section: Ndi‐based Polymer Semiconductorsmentioning
confidence: 99%
“…Amongt he series, 47 b with 2-butyloctyl chain displayed aw ell-organized packings tructure and favorable domain size when mixed with D1 polymer,l eadingt ot he highest PCE of 4.25 %. [58] Chen et al also reported two NDI polymers 48 a and 48 b with at hiophene moiety on the alkyl side chains, whichl ed to ab roadened absorption and suppressed aggregation of the materials, thus yielding aP CE of 4.75 %. Alkoxy chain containingN DI molecules were first reported by Sullivane tal.…”
Section: Introductionmentioning
confidence: 99%